Infrastructure Performance and Reform in Developing and Transition Economies : Evidence from a Survey of Productivity Measures - Estache, Antonio; Perelman, Sergio; Trujillo, Lourdes (World Bank, Washington, DC, 2012)
The authors review about 80 studies on electricity and gas, water and sanitation, and rail and ports (with a footnote on telecommunications) in developing countries. The main policy lesson is that there is a difference in the relevance of ownership for efficiency between utilities and transport in developing countries. In transport, private operators have tended to perform better than public operators. For utilities, ownership often does not matter as much as sometimes argued. Most cross-country studies find no statistically significant difference in efficiency scores between public and private providers. As for the country-specific studies, some do find differences in performance over time but these differences tend to matter much less than a large number of other variables. Across sectors, private operators functioning in a competitive environment or regulated under price caps or hybrid regulatory regimes tend to catch up best practice faster than public operators. There is a very strong case to push regulators in developing and transition economies toward a more systematic reliance on yardstick competition in a sector in which residual monopoly powers tend to be common.